2018
DOI: 10.1111/pbr.12583
|View full text |Cite
|
Sign up to set email alerts
|

Yield stability studies of soybean (Glycine max (L.) Merrill) under rhizobia inoculation in the savanna region of Nigeria

Abstract: Soybean (Glycine max (L.) Merrill) production is expanding into temperate and tropical environments. Yield stability studies under rhizobia inoculation were investigated in 24 soybean genotypes over two successive growing seasons at three agro-ecological zone of Nigeria, during the 2015-2016 rainy seasons. Treatments were arranged in a split-plot design and replicated three times. Treatments were 24 soybean genotypes and three levels of rhizobia inoculation. Results indicated that the variation of genotypes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…In other studies, different soil conditions can also influence the genotype responses of yield in crop plants (Prayoga et al, 2021). Tolorunse et al (2018) reported that significant environmental differences are the critical cause of the emergence of GEI in soybean and other crops. Therefore, the existence of GEI can make the plant selection process difficult.…”
Section: Introductionmentioning
confidence: 98%
“…In other studies, different soil conditions can also influence the genotype responses of yield in crop plants (Prayoga et al, 2021). Tolorunse et al (2018) reported that significant environmental differences are the critical cause of the emergence of GEI in soybean and other crops. Therefore, the existence of GEI can make the plant selection process difficult.…”
Section: Introductionmentioning
confidence: 98%
“…Climate change may make it more difficult to cultivate crops in the same way and regions as in the past. The impacts of climate change must be weighed against other chang-2 of 13 ing elements that affect agricultural productivity, such as changes in farming techniques and technology [5,6]. Protein and oil contents in soybeans are two of the most important seed quality factors that soybean breeders, growers, and marketers take into account.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, phenotypic stability of distinct traits, either yield or quality traits, is the ability of a genotype to perform consistently in various environments [12]. It is worth noting that determining the stability pattern of genotypes is a prerequisite for understanding their response to different environments, identification of stable and widely adapted genotypes, and breeding new cultivars that could adapt to the different environments [12,13]. Thus, plant breeders' always aim to select varieties with high performance across different environments.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, studies such as the one presented in this work become quite relevant since the agricultural frontier for soybean cultivation has increased in the northeast region of Brazil, as has the demand for adapted cultivars. The presence of cross-interaction has also been mentioned by several authors when evaluating soybean cultivars under different edaphoclimatic conditions (8,11,23,26,33).…”
Section: Table 3 Deviance Analysis Estimates Of Variance Components A...mentioning
confidence: 77%
“…This is not commonly observed duirng the evaluation of soybean genotypes in various environments. Generally, for soybeans, the effect of genotypes has a greater effect on the phenotype (3,5,22,26,33).…”
Section: Table 3 Deviance Analysis Estimates Of Variance Components A...mentioning
confidence: 99%